Farmers Willingness To Pay for Privatized Agricultural Services: An Analysis with Plantation Growers - P., Chellattan Veettil; K., Venkataranga Naika (Indian Journal of Extension Education, 2009)
Agricultural extension system all over the world is under constant revision and change to adapt with the new challenges and need of the farmers. Krishi bhawan the system of extension in Kerala which was established in 1987 by the State Government has been analyzed in the present study to check the farmers perception on it’s performance and analyze the scope of privatizing extension services. It is found that only 35 per cent of the farmers perceived that the Krishi Bhawan’s performance was good. The willingness to pay for alternative extension service is estimated by using double bounded dichotomous choice model using contingent valuation method and it show a high amount of Rs. 113.07 per visit of the extension service provider. This revealed that there is a scope for private extension service in Kerala where extension is mainly through public extension system.